Exploring The Roots Of Materialism And The Religious Crisis: An Islamic Perspective - Lestari, Widia; Aprilia, Nindy Putri; Parhan, Muhammad (Tatar Pasundan: Jurnal Diklat Keagamaan, 2024)
The industrial revolution 4.0 has transformed life paradigms by integrating digital and physical technologies, requiring problem-solving to be precise, accurate, and grounded in scientific methods. This era faces significant challenges from the growing ideology of materialism, which emphasizes empirical values as the center of existence. Consequently, realities beyond the material realm, including the existence of God, are often dismissed, posing a serious threat to Indonesian society, where belief in God forms the philosophical foundation of national life. This study employs a library research method to investigate the roots of declining religious attitudes globally, partly driven by the widespread influence of materialism. Through an ontological approach, the study finds that materialism emerged as a critique of mythocentric views and speculative science. However, from an Islamic perspective, reality is not confined to the material; immaterial entities are equally real and integral to human life. Islamic logic points to a causal relationship where all existence must originate from a primary cause—the All-Existent (God). Thus, materialism's rejection of God stems from its limited understanding of existence as purely material. Keywords: materialism; ontology; islamic perspective